2013
DOI: 10.1371/journal.pone.0061077
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spot Sampling for Hepatitis B Virus Serology and Molecular Testing

Abstract: Background & AimsDried blood spots (DBS) on filter paper have been successfully used to diagnose and monitor several infectious diseases. The aim was to investigate the performance of DBS in hepatitis B virus (HBV) diagnosis using commercial tests in comparison to standard methods.MethodsPaired DBS and plasma samples were collected from 200 patients: 100 patients with HBsAg negative status and 100 patients with HBsAg positive status. In the latter patient, HBeAg reactivity was tested. Ten samples of anti-HBs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 38 publications
4
62
1
Order By: Relevance
“…After diluting samples to lower levels of viremia, they estimated a limit of detection in DBS of 914.1 IU/ml (standard deviation, 157.8). 7 Similar to our results, Mohamed and others reported that DBS samples had consistently lower HBV viral loads compared to plasma, with those differences ranging from 0.65 to 1.0 log IU/ml. 6,7 The average difference in viral load between sample types in our study (1.59 log IU/ml) was not unexpected since DBS have smaller input volumes of 75–100 μL of whole blood (approximately half of which is comprised of plasma) versus 650 μL used in plasma testing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After diluting samples to lower levels of viremia, they estimated a limit of detection in DBS of 914.1 IU/ml (standard deviation, 157.8). 7 Similar to our results, Mohamed and others reported that DBS samples had consistently lower HBV viral loads compared to plasma, with those differences ranging from 0.65 to 1.0 log IU/ml. 6,7 The average difference in viral load between sample types in our study (1.59 log IU/ml) was not unexpected since DBS have smaller input volumes of 75–100 μL of whole blood (approximately half of which is comprised of plasma) versus 650 μL used in plasma testing.…”
Section: Discussionsupporting
confidence: 92%
“…Suboptimal elution of nucleic acids from the filter paper is another explanation for the difference between DBS and plasma viral loads. In this study, we used manual elution methods but other studies 7 have utilized automated platforms to optimize the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown decreased sensitivity of DBS compared to plasma in samples with lower viral loads[20,28,29]. In our study, we estimated that the LLD was below 500 copies/mL for HIV-RNA, 100 IU/mL for HCV-RNA and 200 IU/mL for HBV-DNA by DBS testing.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have shown that DBS can be used to reliably measure human immunodeficiency virus (HIV) RNA viral load [68] and hepatitis C virus (HCV) RNA viral load [911]. However, only a few smaller studies, and none in low-income countries, have assessed the performance of DBS for HBV DNA quantification and applied it in patient management [1215]. …”
Section: Introductionmentioning
confidence: 99%